Applications of the Dopaminergic System Expressed by Peripheral Blood Lymphocytes in Neuropsychiatric Disorders - Ambar Shuaib, Muazzam Ahmad, Amber Asfandyar, Zakia Subhan, Abdur Razaq, Sudhair Abbas Bangash, Muhammad Khurram, Aroob Idrees, Zakir Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Dopamine (DA) is essential for the central nervous system (CNS) regulation of neurological, psychological, behavioral, and hormonal processes. Objective: In order to establish the viability of peripheral blood lymphocytes (PBL) as a molecular tool for examining DA dysregulation in neurological diseases, this research sets out to establish current characterization of the DA system in PBL. Methods: This study was carried out at Khyber teaching hospital from Jan 2022 to April 2022. Twenty-three (23) patients suffering with Parkinson’s disease (PD) participated in that research (average age 56 years, mean disorder length 28 months). Nine of these participants received treatment with direct dopamine agonist medications, whereas the other 14 patients were drug-naive (levodopa-naive group). Results: Norpramin, a noradrenaline uptake blocker, established its efficacy at dosages numerous times elevated than blockers of dopamine uptake, but the serotonin uptake inhibitor Prozac was inactive. Dopamine transporter immunoreactivity levels varied significantly across groups, according to the ANOVA analysis (KW=27, P=0.001). Conclusion: PBL may function as a biological probe to identify DA transmission disruption in neuropsychiatric illnesses and to track the efficacy of pharmaceutical therapies Keywords: dopamine, dopaminergic system, peripheral blood lymphocytes, neuropsychiatric disorders